Exploring Psychological State and Performance Within the Speech Contest EFL Competitors - Wardana, I Ketut; Adi Susrawan, I Nyoman; Sukanadi, Ni Luh (ETERNAL (English Teaching Journal), 2024)
Research into the mental well-being of students participating in English speech competitions and its influence on their performance is limited. Thus, this investigation aimed to analyze and compare the mental conditions, including depression, anxiety, and stress, among English speech contestants. Using a quantitative approach with a correlational design, the research included a sample of 60 participants. from 60 schools in Badung Regency. Given the population size was under 100, all participants were included, though 21 were later disqualified, resulting in 39 eligible competitors. Research tools encompassed a 7-minute English speech test and a Depression Anxiety Stress (DAS) questionnaire. Analysis entailed descriptive techniques, including correlation and simple regression t-tests. Initial findings revealed that 54% of participants experienced "mild" depression, 95% encountered "moderate" anxiety, and 59% underwent "mild" stress. Moreover, 58% performed "very well," while 43% presented "well" in their speeches. Notably, a significant correlation existed (depression (r= 0.661), anxiety (r= 0.867), stress (r= 0.929)) between psychological pressure and speech performance. The findings emphasize the need to bolster participants’ confidence and alleviate apprehension as lower levels of anxiety and stress were associated with better speech performance.